Perancangan Sistem Informasi Akuntansi Kas pada Business Center Yayasan Perguruan Daarussalaam Jagakarsa - Naeda, Naeda Shifa Silvia; Gurendrawati, Etty; Khairunnisa, Hera (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
The study conducted at the Business Center (BC) of Yayasan Perguruan Daarussalaam Jagakarsa found that the accounting system in use had not yet adopted digital technology, with cash receipts and disbursements still recorded manually using a ledger book. This practice increases the risk of recording errors and data inconsistencies. Moreover, BC administrators faced difficulties in bookkeeping due to a lack of accounting background and training. To address these issues, the researcher designed a Microsoft Excel-based accounting information system tailored to the organization's needs. This study employed a qualitative method with a case study approach and applying the System Development Life Cycle (SDLC) waterfall model in system development. The findings indicate that the proposed system improves work efficiency, minimizes recording errors, and strengthens transparency and accountability in financial management as a form of responsibility to the foundation.